Fecal microbiota of adolescent and young adult cancer survivors and metabolic syndrome: an exploratory study. (11th October 2022) - Rotz, Seth J.; Sangwan, Naseer; Nagy, Matthew; Tzeng, Alice; Jia, Margaret; Moncaliano, Maria; Majhail, Navneet S.; Eng, Charis
Abstract: Metabolic syndrome and obesity occur commonly in long-term pediatric cancer survivors. The intestinal microbiome is associated with metabolic syndrome and obesity in the general population, and is perturbed during cancer therapy. We aimed to determine if long-term survivors of pediatric cancer would have reduced bacterial microbiome diversity, and if these findings would be associated with components of the metabolic syndrome, obesity, and chronic inflammation. We performed a cross-sectional exploratory study examining the intestinal microbiome via 16S amplicon sequencing, treatment history, clinical measurements (blood pressure, body mass index) and biomarkers (hemoglobin A1c, lipoproteins, adiponectin: leptin ratio, C-reactive protein, TNFα, Interleukin-6, and Interleukin-10) between 35 long-term survivors and 32 age, sex, and race matched controls. All subjects were aged 10–40 years, and survivors were at least five years from therapy completion. Survivors had lower alpha diversity compared to controls (Shannon index p = .001, Simpson index p = .032) and differently abundant bacterial taxa. Further, among survivors, those who received radiation (18/35) to the central nervous system or abdomen/pelvis had decreased alpha diversity compared to those who did not receive radiation (Shannon and Simpson p < .05 for both). Although, no specific component of metabolic syndrome or cytokine was associated with measures of alpha diversity, survivors with low adiponectin–lectin ratio, elevated body mass index, and elevated C-reactive protein had differently abundant taxa compared to those with normal measures. The microbiome of cancer survivors remains less diverse than controls even many years after diagnosis, and exposure to radiation may lead to further loss of diversity in survivors. Supplemental data for this article is available online at https://doi.org/10.1080/08880018.2022.2049937